Growth of individual trees of Geoffreea decorticans Burk. in a forest from the Semiarid Chaco, Argentina - Giménez, Ana María; Hernández, Patricia; Ríos, Norfol; Calatayu, Federico (Instituto de Ecología, A.C., 2013)
The objective of this study was to improve the knowledge on the annual growth rates of Geoffreeadecorticans (chañar), to define the evolution of annual growth increment (IR), diameter at breast height(DAP), normal section (DN) with age, to estimate mean annual (IMA) and annual increment (IA) in orderto propose guidelines for proper management of the species. The study was carried out in a semiaridChaco forest, at Quebrachos Park, Alberdi, Santiago del Estero Province, Argentina. For epidometricstem analysis, 16 vigorous trees were selected based on DAP greater than 15 cm and clean bole. Fromeach tree cross-sections of 5 cm thickness were removed at 0,30 m; 1,30 m above ground, and at theend of the stem. Definition of ring boundaries and ring with measuring were made with computerizedequipment ANIOL and the computer program CATRAS. The data were analyzed with the statisticalsoftware package INFOSTAT. Chañar presented well-defined annual growth rings. The average thicknessof rings is 5,90 mm (1,79 – 16,55). The age of completion for DAP was determined to be the five years, and NS is achieved after 37 years.This growth rate can define the managementon short rotations.